Training Enhances Immune Cells Mitochondrial Biosynthesis, Fission, Fusion, and Their Antioxidant Capabilities Synergistically with Dietary Docosahexaenoic Supplementation. (6th September 2016) - Busquets-Cortés, Carla; Capó, Xavier; Martorell, Miquel; Tur, Josep A.; Sureda, Antoni; Pons, Antoni
Abstract : Exercise training induces adaptations in mitochondrial metabolism, dynamics, and oxidative protection. Omega-3 fatty acids change membrane lipid composition and modulate mitochondrial function. The aim was to investigate the effect of 8-week training and docosahexaenoic acid (DHA) supplementation (1.14 g/day) on the mitochondria dynamics and antioxidant status in peripheral blood mononuclear cells (PBMCs) from sportsmen. Subjects were assigned to an intervention (N = 9 ) or placebo groups (N = 7 ) in a randomized double-blind trial. Nutritional intervention significantly increased the DHA content in erythrocyte membranes from the experimental group. No significant differences were reported in terms of circulating PBMCs, Mn-superoxide dismutase protein levels, and their capability to produce reactive oxygen species. The proteins related to mitochondrial dynamics were, in general, increased after an 8-week training and this increase was enhanced by DHA supplementation. The content in mitofusins Mtf-1 and Mtf-2, optic atrophy protein-1 (Opa-1), and mitochondrial transcription factor A (Tfam) were significantly higher in the DHA-supplemented group after intervention. Cytochrome c oxidase (COX-IV) activity and uncoupling proteins UCP-2 and UCP-3 protein levels were increased after training, with higher UCP-3 levels in the supplemented group. In conclusion, training induced mitochondrial adaptations which may contribute to improved mitochondrial function. This mitochondrial response was modulated by DHA supplementation.